(untitled) (Orfeu, 2017)
This article analyses partial results of doctoral research developed in an early childhood public center selected by random sampling. The study shows the dynamics of interactions involved in classroom singing. The data was collected through observation of classroom routines. The fieldwork was developed in different months in order to avoid associating the results with events in the academic calendar. This study reveals the impact of songs and singing on the children’s and instructors’ own identities. The study also helps illustrate the role of song as social discourse, producing perverse effects if used as a control mechanism, and clearly showing the dynamics of the teachers’ power.